PENGEMBANGAN E-MODUL MODEL PEMBELAJARAN CINQASE BERBASIS FLIP PDF PROFESSIONAL UNTUK MENINGKATKAN HASIL BELAJAR FISIKA PESERTA DIDIK - Hunaidah Hunaidah; La Sahara; Husein Husein; Vivi Hastuti Rufa Mongkito (Jurnal Dedikasi Pendidikan, 2022)
This research is caused by online learning, so that appropriate teaching materials are needed to support learning. This study aims to develop e-physics with the CinQASE model assisted by a professional flip pdf application that meets the valid, practical and effective criteria. This study uses the R&D (Research and Development) research method with a 4D development model (Define, Design, Develop, and Disseminate). The research object was the students of Senior High School Tahfidzul Qur'an Mu'adz Bin Jabal, which amounted to 54 students. Data collection techniques used validation sheets, questionnaires, and written tests. The feasibility e-module is assessed based on the validity of the e-module as seen from the assessment of 3 validators, the practicality e-module is seen from the evaluation of student responses, and the effectiveness e-module is seen from the increase in learning outcomes. The results showed that the CinQASE e-module with the professional flip pdf application developed was declared feasible with a validity result of 3.67 with a very good category. The results of the practicality of the e-module from student responses are 3.20 for class X-Putra and 3.21 for Class X-Putri with a very good category. The effectiveness results with n gain values of 0.34 (X-Putra) and 0.35 (X-Putri) are included in the good category. The developed e-module is declared feasible and has met the valid, practical, and effective criteria